G100(P) How do we encourage a change of behaviour around colleagues taking breaks?. (25th October 2020) - Baverstock, A; Stewart, L; White, C
Abstract : We relaunched our HALT (are you Hungry, Angry, Late or Tired?) campaign with poster and enhanced communications. To change behaviour around break culture more was needed. Aim: To increase colleague wellbeing by improving the percentage of colleagues taking a break. Methods: As part of our wellbeing conference we ran a HALT workshop. Including some background information around the positive benefits of taking a break, barriers and enablers to taking a break. We captured baseline data at beginning of the conference and collected post conference data. Ongoing data collection to see if changes have been sustained. Results: 91 colleagues attended our workshop. We asked on a Likert style scale how energised they felt from low – high to 9 low energy levels. At the beginning of the shift 3/9 (range 1–7) and at the end 5/9 (Range 1–9). Barriers and enablers to taking a break were at organisation, team and individual level. Enviromental factors included 'no staff room', 'always connected to technology'. Workload pressure was also an issue 'the squeeze'. 'Unexpected work' and 'lack of wiggle room' alongside 'staffing shortages' made planning difficult. 'Peer pressure' to keep working and 'not being seen as a human being' with a sense of 'personal guilt' need to be addressed. Environment: 'nice staff room' and 'ability to hand bleep over' with 'scheduling breaks as a team'. Leaders also need to role model alongside 'giving yourself permission'. We all need to find 'courage to have break uninterrupted'. Discussion: Our workshop shows there are barriers and enablers to taking a break. Changes are needed as individuals but more importantly as teams and organisations to enable all colleagues to feel empowered to take their breaks. Our workshop has shown an improvement in number of colleagues taking a break. We are now planning the next stage to roll out wider.